Brazilian Pseudochironomini (Diptera: Chironomidae) Part 2. New Pseudochironomus and Riethia species - Trivinho-Strixino, Susana; Shimabukuro, Erika Mayumi (Zootaxa, 2018)
In this second part of the study about Brazilian Pseudochironomini Sæther (Diptera: Chironomidae: Chironominae), seven new species are described and illustrated. Three species belong to the genus Pseudochironomus; they are: Pseudochironomus capivara sp. n., Pseudochironomus ariquemis sp. n. and Pseudochironomus boraceia sp. n. all are described from males, the first as pupa, the second as larva and pupa also. Four species belong to Riethia: Riethia cauame sp. n., Riethia fazzari sp. n., Riethia galilei sp. n. and Riethia pantera sp. n. all described as male. Except for R. fazzari sp. n. and P. boraceia sp. n. collected in São Paulo State, the remaining species were collected in Amazon region. A key of males to known species of Brazilian Pseudochironomini is given.